Diagnosis and Management of Leprosy - Medhi Denisa Alinda; Silvani Geani; Regitta Indira Agusni; Bagus Haryo Kusumaputra; Novianti Rizky Reza; Cita Rosita Sigit Prakoeswa; Muhammad Yulianto Listiawan (Faculty of Medicine, Universitas Airlangga, 2020)
Background: Leprosy is a chronic infectious disease caused by Mycobacterium leprae, which tends to attack peripheral nerves and skin. The diagnosis of leprosy is based on the presence of one of three cardinal signs. Early diagnosis of leprosy is critical and is made through clinical examination and investigation. Purpose: To discuss the diagnosis, laboratory examination, and treatment of leprosy, considering that early diagnosis and appropriate treatment are the key elements in breaking the chain of transmission and preventing leprosy patients' disabilities. Review: Leprosy is a chronic granulomatous infectious disease caused by the Mycobacterium leprae. Based on clinical appearance, histopathology findings, and immunological, leprosy is grouped into six forms using the Ridley-Jopling classification, namely Tuberculoid (TT), Borderline Tuberculoid (BT), Borderline-borderline Mid-borderline (BB), Borderline-lepromatous (BL), Subpolar Lepromatous (LLs), and Polar Lepromatous (LLp). Based on the treatment category, leprosy is grouped into paucibacillary (PB) and multibacillary (MB). Leprosy is often diagnosed clinically, and skin scraping smear remains the preferred laboratory method. The negative results of smear skin scraping may not necessarily exclude leprosy. Therefore, a higher sensitivity test might be needed to detect M. leprae. Treatment with Multi-Drug Therapy (MDT) is adjusted based on the type of leprosy, whether it belongs to the PB or MB group. Treatment of PB type, regimens are rifampicin and dapsone, while in MB type, the patients received rifampicin, dapsone, and clofazimine regimens. Conclusion: A proper diagnosis for leprosy, both through physical examination and laboratory examination, is required to determine an effective MDT treatment and break the chain of disease transmission.